Extended sick neonatal score in prediction of mortality of out born neonates: a hospital-based study - Jamoh, Yabom; Begum, Rukeya (International Journal of Research in Medical Sciences, 2023)
Background: A prospective observational study was conducted in Barpeta, India to evaluate the utility of the Extended Sick Neonatal Score (ESNS) in predicting in-hospital mortality of outborn neonates. Methods: Purposive sampling was used to select a sample size of 200 neonates who were assessed upon arrival at the neonatal unit emergency. The babies were followed up till discharge or death and given scores based on ESNS. A score of ≤11 for all term babies and a score of ≤12 for preterm neonates were found to best predict mortality. Results: Among the 16 total deaths, 12 occurred among full-term neonates, while 4 occurred among preterm neonates. Birth asphyxia was the leading indication of neonatal mortality. ESNS can predict ‘in-hospital mortality’ outcome with satisfactory sensitivity and specificity. For term babies, ESNS of ≤11 had the best sensitivity (93.48%) and specificity (80.92%), AUC (95% CI) was 0.845 (0.772 to 0.902) and for preterms, ESNS ≤12 had the best sensitivity (92.57%) and specificity (79.48%), AUC (95% CI) was 0.729 (0.609 to 0.829). Conclusions: ESNS can predict ‘in-hospital mortality’ outcome with satisfactory sensitivity and specificity. It has the advantage of being easy to score with minimal resources in both term and preterm neonates when applied early during the course of hospitalization. It could also be a tool to compare performance of SNCUs.